POTENSI BAKTERI Lactococcus lactis DAN Lactobacillus casei TERHADAP PERFORMA PRODUKSI AYAM PETELUR YANG DIINFEKSI Escherichia colii - Rifqi Najwan; Nabil Fariz Noorrahman; Hana Cipka; Khoirul Huda; Mirni Lamid; Widya Paramita Lokapirnasari (Universitas Tribhuwana Tunggadewi, 2019)
The purpose of this study was to find the effect combination probiotic Lactococccus lactis and Lactobacillus casei on the laying hens infected with bacteria Escherichia coli on feed consumption and feed conversion ratio (FCR). The materials used in this experiment were 120 laying hens aged 25 weeks. Feeds were used commercial concentrate produced by PT. New Hope East Java, type 7183A. In this study were added of six treatments that is (a0b0) chicken without infection and without treatment, (a0b1) chicken without infection plus Antibiotic Growth Promoter (AGP), (a0b2) chicken without infection plus probiotic, (a1b0) chicken infection without treatment, (a1b1) chicken infection plus AGP. (a1b2) chicken infection plus probiotic. Each treatment was repeated four times. The variables measured were are feed consumption (g/bird/day) and feed conversion ratio (%). Data were analyzed statistically using Analysis of Variance (ANOVA), if between treatment showed significant effect were analysed by Duncan’s Multiple Range Test (DMRT). The result of this research shows that the use of probiotic Lactococccus lactis and Lactobacillus casei on the laying hens infected with bacteria Escherichia coli give a real distinction ( P0,05) towards feed consumption and showed a real distinction (P 0.05) towards feed conversion ratio. Based on the results of this research, it can be concluded that the addition of probiotic Lactococccus lactis and Lactobacillus casei on the laying hens infected with bacteria Escherichia coli can improve feed consumption, feed conversion ratio (FCR) of laying hens, hen day production (HDP) and egg weight.